Concept and Types of Administrative Restrictions within Legal Regulation of Economic Activity - M. V. Starynskyi (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on studying the concept of administrative restrictions used by state-authorized agencies in the process of regulating economic activity. Based on the analysis of scientific sources and the practice of legal regulation of economic activity, it has been emphasized that the category of “administrative restrictions” in modern legal science is mainly used to denote the result of relations related to the offense. It has been concluded that such an approach is controversial, and the approach when administrative restrictions are studied through the category of “coordination” is more appropriate. State-authorized agencies in order to ensure the public interest use a large number of administrative restrictions in the field of economic activity, which are formulated as individual (subjective) measures of administrative and legal nature defined by regulatory acts and aimed at coordinating the behavior and actions of the addressee in the sphere of economic activity within the appropriate limits that are introduced in order to ensure the public interest. In the course of the research the author has distinguished the features of administrative restrictions used in the legal regulation of economic activity, which include the following: 1) they are objectified in the legal norms contained in the normative legal acts regulating economic activity and having a restrictive nature; 2) they coordinate the activity of economic entities, defining the boundaries, the degree of freedom of choice of their actions; 3) the subject of application is a state-authorized agency in the field of regulation of economic activity, and the addressee is an individual or a legal entity – business entities; 4) the purpose of application is to bring the behavior of the subject in accordance with a certain standard of economic activity; 5) they have mandatory nature and are provided by state coercion.